2014
DOI: 10.1542/peds.2013-1107
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Self-Medication and Over-the-Counter Analgesics for Children

Abstract: OBJECTIVE: Self-medication with over-the-counter (OTC) analgesics, such as paracetamol (PCM), among children and adolescents is increasing and constitutes an important public health issue internationally. Reasons for this development are unclear; parental influence is suggested. Our objective was to examine whether self-medication with OTC analgesics among school-aged children is influenced by maternal self-reported health and medicine use, taking the child’s frequency of pain into account. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 35 publications
6
38
1
11
Order By: Relevance
“…Two studies found that children of parents with chronic pain had increased self-reported medication use for headache [3] and increased odds of emergency department visits and hospitalizations [53] compared to control children. Two other studies found no significant group differences when measuring author-defined newborn risk categories [4] and parent-reported use of over-the-counter analgesics by children [42]. …”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that children of parents with chronic pain had increased self-reported medication use for headache [3] and increased odds of emergency department visits and hospitalizations [53] compared to control children. Two other studies found no significant group differences when measuring author-defined newborn risk categories [4] and parent-reported use of over-the-counter analgesics by children [42]. …”
Section: Resultsmentioning
confidence: 99%
“…Research points out that a family's methods of managing pain and illnesses are evident in teenagers' OTC use (Skarstein, Lagerløv, Kvarme, & Helseth, 2016), with particular reference to maternal behavior (Jensen et al, 2014).…”
Section: The Influence Of the Social Groupsmentioning
confidence: 99%
“…Family strategies for pain treatment seem to influence teenagers’ use of OTCAs. Further, parental attitudes regarding OTCAs are found to be associated with the adolescents intake of such medication (Jensen et al, ). The International Association for the Study of Pain (IASP) Task Force on Taxonomy defined pain as: “an unpleasant sensory and emotional experience associated with actual or potential tissue damage or described in terms of such damage” (Merskey, :S74).…”
Section: Introductionmentioning
confidence: 99%